A two-factor scale of perceived power - Myojoong Kim; Frank May (PLoS ONE, 2025)
Power-the capacity to influence outcomes-manifests in two distinct forms: social power, defined as the perceived ability to control others’ behaviors and decisions, and personal power, characterized by the capacity to resist unwanted external influence and maintain autonomy. Theoretically, these dimensions are rooted in different needs, and thus are likely to differentially predict certain behaviors. However, existing measures often conflate these dimensions, limiting insights into their unique behavioral effects. To address this issue, the present research has developed and validated a two-factor scale of perceived power to completely capture both facets of power across twelve studies (N =  2,878). Exploratory and confirmatory factor analyses support the scale’s structure, while reliability and validity tests demonstrate its robustness. Following assessments of the structure of the scale, its validity was demonstrated across multiple studies: Study 1 establishes the orthogonality of personal and social power through experimental manipulation, Study 2 reveals that personal power increases proactive advice-seeking, whereas social power reduces the tendency to solicit advice, and Study 3 demonstrates that social power amplifies negative reactions to service failures, while personal power does not. These divergent outcomes underscore the distinct roles of personal and social power, highlighting the scale’s utility for advancing research.